2010
DOI: 10.1007/s11049-010-9095-z
|View full text |Cite
|
Sign up to set email alerts
|

A model of lexical variation and the grammar with application to Tagalog nasal substitution

Abstract: This paper presents a case of patterned exceptionality. The case is Tagalog nasal substitution, a phenomenon in which a prefix-final nasal fuses with a steminitial obstruent. The rule is variable on a word-by-word basis, but its distribution is phonologically patterned, as shown through dictionary and corpus data. Speakers appear to have implicit knowledge of the patterning, as shown through experimental data and loan adaptation. A grammar is proposed that reconciles the primacy of lexical information with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…From this they conclude that the acquisition of UG-motivated sound patterns has an analytic advantage compared to less natural ones. Zuraw (2000Zuraw ( , 2010 found a similar effect in Tagalog. In the native lexicon, the nasal substitution alternation at the prefix-stem boundary applies with greater frequency and reliability to stems beginning with a voiceless stop compared to the corresponding voiced one: e.g.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…From this they conclude that the acquisition of UG-motivated sound patterns has an analytic advantage compared to less natural ones. Zuraw (2000Zuraw ( , 2010 found a similar effect in Tagalog. In the native lexicon, the nasal substitution alternation at the prefix-stem boundary applies with greater frequency and reliability to stems beginning with a voiceless stop compared to the corresponding voiced one: e.g.…”
Section: Introductionmentioning
confidence: 76%
“…H-J. Kim (2012) attributed both the novel word results and the loanword accent to the action of UG constraints trained on the statistics of the lexicon, employing the USE LISTED model of Zuraw (2000Zuraw ( , 2010. In the final section of the paper, we questioned the suitability of this model for our South Kyengsang data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, lexical encoding/listing alone is not sufficient to explain speakers' knowledge of unpredictable alternations, since such processes often show some degree of productivity. Productivity shows that speakers have extrapolated knowledge that goes beyond the specific stems involved; speakers must also have grammatical rules or constraint rankings for exceptionful or irregular processes (Kenstowicz & Kisseberth 1977;Zuraw 2000Zuraw , 2010Albright & Hayes 2003;Hayes & Londe 2006;Pater et al 2012). Furthermore, it has been observed that in many cases, the productivity of an alternation reflects the relative frequency of that pattern in the lexicon.…”
Section: Introductionmentioning
confidence: 99%